Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am tagging this as multivariable calculus because it potentially involves taking partial derivatives.

I am working on some mathematical treatment for Cournot duopoly models (not homework, just preparing for a test tomorrow). A simple two player Cournot model is of the form $p=1000-q_1-q_2$ where $p$ stands for price, and $q_i$ is the quantity produced by firm $i$. The payoffs of each firm are given by $pq$ minus some marginal cost times $q$, say $-10q$. In this case, to find best response for firm $i$, I would take its payoff function $\pi_i=(1000-q_i-q_j)q_i-10q_i$ and take its derivative with respect to $q_i$, getting $1000-2q_i-q_j-10$. I would then set it equal to $0$, solving for $q_i$, and getting $q_i=\frac{990-q_j}{2}$, thus getting an expression maximizing $\pi_i$ in terms of $q_j$. Doing the same thing with $q_j$, I get $q_j=\frac{990-q_i}{2}$ since the function is symmetric. Then I set equations equal to each other/substitute one into the other, and get the Nash equilibrium (profit maximization for both), easy.

The issue I am having is dealing with $n$ firms. Assume a>c>0, b>0. Suppose we have total quantity of output $Q=\sum_{i=1}^{n} q_i$ and price be given as $p=a-bQ$. Then let profit of firm $i$ be defined as $\pi_i=p(Q)q_i-cq_i=(a-bQ)q_i-cq_i$. Defining $Q_{-i}$ to denote the sum of quantities of all firms but of firm $i$, we can rewrite the profit function of $i$ as $\pi_i=(a-bq_i-bQ_{-i})q_i-cq_i$ (observe that $q_i+Q_{-i}=Q$). From here on, I can again take a partial derivative with respect to $q_i$, and find the payoff maximization function to be $\pi_i'=a-2bq_i-bQ_{-i}-c$. Rewriting for $q_i$, I get $q_i=\frac{a-bQ_{-i}-c}{2b}$. So, for an arbitrary firm $j$, the maximization function in terms of $Q_{-j}$ will be given by $q_j=\frac{a-bQ_{-j}-c}{2b}$.

The problem I have here is that I can't anymore substitute as easily as I did in the first example with only two firms. The book gives me a hint: Summing the best-response functions over the different players will help. I do not know what to make of it. Could you explain how to find an intersection given $n$ such functions in the form presented above?

EDIT: I might be onto something here, feedback appreciated!

So I decided to follow the books advice and see what comes of it. Summing both sides of $q_i=\frac{a-bQ_{-i}-c}{2b}$ over all the players I get $q_1+\dots +q_n=Q=\frac{na}{2b}-\frac{nc}{2b}-\frac{(n-1)(q_1+\dots + q_n)}{2} \to 2Q=\frac{na}{b}-\frac{nc}{b}-(n-1)(q_1+\dots + q_n)$=$\frac{na}{b}-\frac{nc}{b}-(n-1)(Q) \to (n+1)Q=n\frac{(a-c)}{b} \to Q=\frac{n}{n+1} \frac{(a-c)}{b}$. Thus $q_i=\frac{n}{n+1} \frac{(a-c)}{b} - Q_{-i}$. Hopefully I am at least on the right track, though I can't see where this leads me yet.

share|improve this question
    
I think you get it. –  GWu Apr 19 '11 at 4:29

1 Answer 1

up vote 3 down vote accepted

As you pointed out, $q_i+Q_{-i}=Q$. Summing over all $i$ yields $$Q+\sum_i Q_{-i}=nQ.$$ Then sum over all $j$ for the best-response functions: \begin{eqnarray} Q&=&\sum_{j}q_j=\frac{n(a-c)}{2b}-\frac 1 2 \sum_{j}Q_{-j}=\frac{n(a-c)}{2b}-\frac 1 2(n-1)Q\\ \Rightarrow Q&=&\frac{n(a-c)}{(n+1)b}. \end{eqnarray} From here, you can solve for $Q$, and then get each $q_i$ because \begin{eqnarray} q_i&=&\frac{a-bQ-c}{2b}+\frac{q_i}2\\ \Rightarrow q_i&=&\frac{a-bQ-c}{b}=\frac{a-c}b-Q\\ &=&\frac{a-c}b-\frac{n(a-c)}{(n+1)b}=\frac{a-c}{b(n+1)}. \end{eqnarray}

share|improve this answer
    
@GWu: Thanks! I just did that, and edited my post -- it brought me to something. I am not sure if that helps me much though because just as when I started, I have $q_i$ in terms of fractions and $-Q_i$. How do I get a Nash equilibrium from here? I could have presumably gotten it from $q_i=\frac{a-bQ_{-i}-c}{2b}$ too, then... –  gametheorist Apr 19 '11 at 4:30
    
I just edited mine too since I guessed you didn't figure out this. –  GWu Apr 19 '11 at 4:32
    
@GWu: I see how you got to that equation since adding $$\frac{q_i}2$$ to the rest of the equation results into $$\frac{a-bQ_{-i}-c}{2b}$$. Now, if I understand correctly this is better because I can plug in any $q_j$ into the equation since the equation is now dependent on total quantity and not $Q_{-j}$? –  gametheorist Apr 19 '11 at 4:39
    
And plugging in everyone's best response into that one function I get $$q_i=\frac{a-b(n\frac{(a-bQ-c)}{2b}+\frac{Q}{2})-c}{2b}+\frac{q_i}2$$, am I correct? –  gametheorist Apr 19 '11 at 4:44
    
Not that complicated. You have already found what $Q$ is. I wrote down the complete solution. –  GWu Apr 19 '11 at 4:46

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.